Chemical constituents of three bacterial species (enterobacter cloacae, burkholderia cenocepacia and serratia marcescens) and a plant species (crotalaria pallida) / Yap Ann Chee - Yap, Ann Chee (2015)
The present dissertation work focused on the phytochemical studies of a leguminous plant Crotalaria pallida and three bacterial species i.e. Enterobacter cloacae, Burkholderia cenocepacia and Serratia marcescens. C. pallida, from the family of Fabaceae, is a perennial subshrub-like herb known to produce pyrrolizidine alkaloids such as monocrotaline. E. cloacae, B. cenocepacia and S. marcescens are Gram-negative bacteria which are found naturally in the environment and also as opportunistic pathogens known to cause diseases. However, useful natural products with properties such as antibacterial, antifungal or anti-nematodal have been isolated from previous studies.1-4 Eleven compounds were isolated from the hexane extract of C. pallida which included a new compound CM1, a furanone and several lipids. A total of eight compounds including two new compounds EC1 and EC2 were isolated from E. cloacae. Three compounds were isolated from B. cenocepacia including one compound BC1 isolated for the first time from natural resources. Two compounds were isolated from S. marcescens which included the compound SM1 that was reported here for the first time from this bacterial species. All three bacterial species produced a common compound EC3 which was identified as a diketopiperazine. Several of these compounds were selected for bioactivity evaluations for their cytotoxicity against three human cell lines (human colon adenocarcinoma cell line HCT 116, human prostate adenocarcinoma cell line PC-3 and human fibroblast MRC5).